The impact of Big Data analytics on organizational performance/ Fatimah Ahmad Bahsir and Masitah Ahmad - Ahmad Bahsir, Fatimah; Ahmad, Masitah (Faculty of Information Management, 2021)
Big data analytics is an advanced analytic technique that are applied on big data, and from the analytics, it can help to reveal and leverage business change. The aim of this study is to identify the impact of big data analytics on organizational performance. There are three dependent variables included in this study which comprises of better decision making, new opportunities and cost reductions. On the other hand, the impact of big data analytics on organizational performance is the independent variable. The methodology used in conducting this study is through purposive sampling where the respondents is confined to a specific organization in Selangor state that used big data analytics tools in order to achieve desired information. Findings shows that there is significance correlation between independent variable and dependent variables which resulting the hypotheses developed for this study were accepted.